Cara-Cara Transportation dan Handling Containers - Rubahman Rubahman (Jurnal Kimia dan Kemasan, 1978)
Containers usage in Indonesia still require arrangement for the producers and consumens advantage. Several kinds of containers which often used are papers, corrugated board, plastics, cans bottles andglasses. Containers selection are primary based on the raw material being filled,fillng process contamination, transportation, price and specific gravity. Improper selection transportation and handling will cause the containers and its product become spoiled.